Synergistic antiallodynic effects of pregabalin and thioctic acid in a rat model of neuropathic pain - Zárate, Edith; Granados-Soto, Vinicio; Arias-Carrión, Oscar (Frontiers in Pharmacology, 2025)
BackgroundNeuropathic pain is a chronic and often disabling condition that remains refractory to monotherapy because of limited efficacy and dose-limiting adverse effects. Combination therapies that engage complementary mechanisms of action offer a rational strategy to enhance efficacy while minimizing toxicity. Pregabalin, a ligand of α2δ subunits of voltage-gated calcium channels, reduces presynaptic calcium influx and glutamate release. In contrast, thioctic acid (α-lipoic acid), a potent antioxidant with anti-inflammatory properties, modulates TRPV1 channel expression and activity and inhibits CaV3.2 T-type calcium channels. Both agents exert antiallodynic effects in preclinical models, yet their pharmacodynamic interaction has not been systematically evaluated. Given their distinct but convergent actions on neuronal excitability and pain signalling, quantitative synergy analysis is warranted to define the therapeutic potential of their combined use.MethodsWe evaluated the antiallodynic efficacy of pregabalin and thioctic acid, alone and in combination, in female Wistar rats subjected to L5–L6 spinal nerve ligation. Mechanical withdrawal thresholds were measured using von Frey filaments up to 8 h post-oral administration. Dose–response curves were generated for each monotherapy and its 1:1 fixed-ratio combination. Isobolographic analysis was conducted to quantify pharmacodynamic interactions. All behavioural testing was performed under blinded conditions, and adverse effects were qualitatively monitored.ResultsBoth compounds produced dose-dependent increases in mechanical withdrawal thresholds (antiallodynic effects), with ED50 values of 2.45 ± 0.23 mg/kg for pregabalin and 57.49 ± 5.59 mg/kg for thioctic acid. The 1:1 fixed-ratio combination yielded an ED50 of 15.7 ± 1.0 mg/kg and a maximal %MPE of 72.3% ± 4.8%. Isobolographic analysis demonstrated a synergistic interaction, with an interaction index (γ) of 0.524 (95% CI: 0.41–0.66; p < 0.05 vs. theoretical ED50). No overt adverse effects were observed at combination doses, whereas mild sedation occurred only at the highest pregabalin monotherapy dose.ConclusionThese findings provide robust preclinical evidence that co-administration of pregabalin and thioctic acid produces synergistic antiallodynic effects in a validated model of neuropathic pain. This interaction enables effective analgesia at reduced doses, supporting a potential tolerability advantage. Our data support further investigation of this combination in chronic dosing paradigms, inclusion of both sexes, and clinical translation.